Ecological stability evaluation of tidal flat in coastal estuary: A case study of Liaohe estuary wetland, China. (November 2021) - Li, Haifu; Li, Lifeng; Su, Fangli; Wang, Tieliang; Gao, Peng
Highlights: Established an evaluation index of tidal flat ecological stability ( ECO-CSI ). Urbanization and the traffic road were the key negative artificial factors. The sediment discharge, the precipitation, etc. were the key guarantee factors. The threshold value of the Liaohe River sediment discharge was 792.91×10 4 t y −1 . The threshold value of the scale of traffic roads was 770.9244 hm 2 . Abstract: The tidal flat, located at the forefront of the coastal estuary wetland, serves as a peripheral defense line to maintain the stable ecological function of the estuary wetland. Therefore, the accurate identification of the stable state of a tidal flat is rendered as the decision-making basis for the restoration and management of estuary wetland ecosystems. Conducted at the tidal flat of the Liaohe Estuary Wetland, the study established a comprehensive evaluation index of tidal flat ecological stability ( ECO-CSI ) based on the Pressure-State-Response model and Rough Set theory. The driving factors and threshold values which affected the stability of the tidal flat were identified. The results showed that the average ECO-CSI value of the tidal flat during the past 30 years was 0.44 indicating, in general, a relatively stable state of the tidal flat. On the other hand, in 2017 the ECO-CSI value was 0.25, pointing that the tidal flat is in an unstable state currently. Among the factors affecting the tidal flat ecological stability, the artificial development activities were the major driving factors, and the urbanization and the traffic road scale were the key driving factors leading to the instability of the tidal flat. Of the natural factors, the sediment discharge, the flow in flood season, and the precipitation in the upstreams were the key guarantee factors for maintaining the material supply of the tidal flat. The threshold values for maintaining the ecological stability of the tidal flat in the Liaohe Estuary wetland were determined that the sediment discharge of the Liaohe River should be not less than 792.91 × 10 4 t⋅y -1 and the scale of traffic roads in the tidal flat should be less than or equal to 770.9244 hm 2 . Hence, in the development and utilization of tidal flats and coastal wetlands, unreasonable human development activities should be minimized to avoid damage to the integrity and natural dispositions of the tidal flat. In this way, the stability of the tidal flat could be improved, contributing to the ecological security for the overall stability of the estuary wetland ecosystem.